FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN PREMENSTRUAL SYNDROME (PMS) - Hesty Fitria Wulandari; Entin Jubaedah (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2022)
The percentage of PMS occurrence in Indonesia at the age of 16-45 years is 80-90%. Factors causing PMS occur because of stress levels, diet, and exercise activity experienced by adolescents. Therefore, one of the efforts to prevent the occurrence of PMS symptoms is by changing adolescent lifestyle. This study aims to determine the factors that influence PMS in adolescents.This research uses Cross Sectional. The sample of this study used a total sampling technique with consideration of inclusion and exclusion criteria, total of respondents in this study were 70 College Students Nursing Diploma III Poltekkes Kemenkes Tasikmalaya. Data collection using a questionnaire through Google form which was analyzed by Chi-Square test, Kruskall Wallis, Mann-Whitney.The results showed as many as 55.7% experienced moderate symptoms during PMS, experiencing moderate stress as much as 81.4%, doing enough exercise activity as much as 80%, and doing unhealthy diet as much as 84.3%. Based on the bivariate results the relationship between stress levels with PMS obtained p value 0.102 (p ? 0.05). For the relationship with exercise activity obtained p value 0.900 (p ? 0.05), and for the relationship with diet obtained p value 0.194 (p ? 0.05). So it can be concluded that there is no influence between stress level, exercise activity, and diet with the incidence of PMS in adolescents